The Effect of Managerial Ownership and Institutional Ownership on Sustainability Reporting and Their Impact on Earning Management - Listia Aulia Indy; Lia Uzliawati; Windu Mulyasari (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this study is to examine the effect of managerial ownership and institutional ownership on sustainability reporting and their impact on earnings management. This research is a type of quantitative research using purposive sampling method as a sampling method. The data collected comes from the annual reports of companies in the mining sector and the basic and chemical industry sectors listed on the Indonesia Stock Exchange from 2015 to 2019, with data analysis techniques using IBM SPSS V.20 software for windows. The results showed that managerial ownership had no effect on sustainability reporting, while institutional ownership had no effect on sustainability reporting. Sustainability reporting has a negative effect on earnings management.